Indications and immediate outcomes of caesarean section deliveries at a national referral hospital in Botswana - Kula, Onteletse Cathrine (My University, 2019)
Background Caesarean section (CS) is a major obstetric intervention, performed by obstetricians and doctors for saving lives of women and their newborns from pregnancy and childbirth related complications. There is great concern about the increasing rise in the rate of CS deliveries in both developed and developing countries as unnecessary CS may have adverse impact upon maternal and neonatal health outcomes. The World Health Organization (WHO) considers CS rates of 5-15% to be the optimal range for targeted provision of this life saving intervention. Although Botswana has not done any research on CS rates, it was identified through health facility reports that it has high rates of CS. The aim of this study was to establish the rate, indications and immediate outcomes of CS deliveries for women who delivered at Princess Marina Hospital (PMH) in Botswana. Method This was a descriptive cross-sectional retrospective study. Maternity registers were reviewed, and there were 6737 deliveries of which 1918 were delivered through CS from January to December 2016. Out of the 1918 CS deliveries, 794 records were sampled. Data were collected using a data extraction tool, entered in Epi-Info version 3.3.3 for cleaning, and was then transported into STATA software version 14 for statistical analysis. Appropriate measures of description such as mean, frequencies and percentages were utilized to describe the different variables under study. Indications of CS were presented as frequency distribution. Categorical variables were compared using chi-square test, with 95% confidence levels considered to verify significant difference between variables with a pvalue of <0.05 considered as significant. Records of women who delivered by CS were stratified into quarters (quarter 1-4) and comparisons were also made between obstetric variables and indications of CS. Results The rate of CS deliveries was 28.5%. The most frequent indication of CS deliveries was fetal distress (23.6%), and 145 (18.3%) were adverse outcomes. Maternal complications accounted for 13.1% of all the adverse outcomes and the most common maternal complication was postpartum haemorrhage (95%). There were 30 stillbirths which accounted for 3.8% of the fetal mortalities. Fetal complications were 126 which accounted for 86.9% of all the adverse outcomes, and the most frequent fetal complication was low APGAR score with 74%. Discussion The CS rate identified in this study was higher than the WHO standard recommendation. The high rate of fetal distress diagnosed might be due to over-diagnosis. Therefore, there is need to avail and improve fetal monitoring technological devices such as Cardiotocograph (CTG) that will reduce the over-diagnosis of fetal distress. Furthermore, this high rate of CS deliveries could be a resultant of poor utilization of instrumental vaginal delivery. Therefore, clinicians should be encouraged and motivated to perform instrumental vaginal delivery such as, vacuum and forceps, when appropriate. The policy makers should also consider developing national policy and guideline on appropriate justification of indications for CS deliveries. The considerable maternal complications can be reduced through strengthening antenatal care and family planning services including community health education programmes. Furthermore, it is essential to re-enforce emergency neonatal resuscitative measures in order to reduce the high rate of perinatal morbidities.
A Research Report Submitted to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, in Partial Fulfillment of the Requirements for the Degree of Master of Public Health in Maternal and Child Health August 2019